Gamifikasi Pembelajaran Menyimak: Efektifitas Permainan “Simon Says” dalam Meningkatkan Kemampuan Auditori Siswa - Dakka, Litha Nesidekawati; Alfian, Heri (Indo-MathEdu Intellectuals Journal, 2025)
This study investigated the effectiveness of the "Simon Says" game in improving students' listening skills, specifically focusing on their auditory comprehension abilities. Employing a pre-experimental design with pretest and posttest, the research involved first-year students at SMP Negeri 1 Tirawuta. Data were collected using listening tests administered before and after implementing the "Simon Says" game as a teaching intervention over eight meetings. The results demonstrated a significant improvement in students' listening skills. The mean score increased from 6.43 to 7.93 for comprehension of spoken statements and from 3.8 to 6.5 for comprehension of dialogues. Statistical analysis using a t-test confirmed the significance of these improvements (t-test values of 5.884 and 6.825 for spoken statements and dialogues, respectively, both exceeding the t-tabel value of 2.045 at df=29 and p<0.05). These findings indicated that the "Simon Says" game is an effective gamification strategy for enhancing students' auditory skills in English language learning, making the learning process more engaging and less stressful. It is recommended that English teachers incorporate this game into their listening lessons.